Recognizing Presentations of Pemphigoid Gestationis: A Case Study - Sadie Henry (Case Reports in Obstetrics and Gynecology)
Introduction. Pemphigoid gestationis (PG) is an autoimmune blistering disease that occurs in approximately 1 in 50,000 pregnancies. Failing to recognize PG may lead to inadequate maternal treatment and possible neonatal complications. Case Report. At 18 weeks of gestation, a 36-year-old otherwise healthy Caucasian G4P1 presented with pruritic papules on her anterior thighs, initially treated with topical steroids. At 31 weeks of gestation, she was switched to oral steroids after her rash and pruritus worsened. The patient had an uncomplicated SVD of a healthy female infant at 37 weeks of gestation and was immediately tapered off steroid treatment, resulting in a severe postpartum flare of her disease. Discussion. This case was similar to reported cases of pruritic urticarial papules followed by blisters; however, this patient had palm, sole, and mucous membrane involvement, which is rare. Biopsy for direct immunofluorescence or ELISA is the preferred test for diagnosis. Previous case reports describe severe postdelivery flares that require higher steroid doses. Obstetrical providers need to be familiar with this disease although it is rare, as this condition can be easily confused with other dermatoses of pregnancy. Adequate treatment is imperative for the physical and psychological well-being of the mother and infant.